Transformasi Peran Gender dan Reorganisasi Struktur Sosial: Studi tentang Perempuan Tani dalam Sektor Informal - Syaifudin Suhri Kasim; Juhaepa; Sarpin; Aryuni Salpiana Jabar; Sarmadan (Universitas Halu Oleo (UHO), 2025)
This study aims to analyze how the transformation of female farmers' roles in the informal sector impacts social structure and gender relations within agrarian communities in Konda District, South Konawe Regency. Women who were previously confined to domestic roles are now increasingly active as economic agents in informal sectors, including subsistence agriculture, local trade, and home-based agro-enterprises. Using a descriptive qualitative approach and in-depth interviews with 15 key informants, the study finds that this role transformation has stimulated a reorganization of social structures, particularly through the growing recognition of women’s productive contributions in public community spaces. Findings indicate that despite facing structural barriers such as limited access to resources and double workload burdens, female farmers are developing adaptive strategies based on social networks, symbolic capital, and local cultural values. This process signifies a significant shift in power relations between men and women at both household and community levels. Therefore, inclusive and gender-responsive policies are needed to strengthen the position of female farmers as agents of social transformation and sustainable rural developmen